In vitro The Role of Paclobutrazol in Potato Seed Production (Solanum tuberosum L) cultivar Granola Kembang Early Generation (G0) In Vitro: Potato - Hot Setiado; Purba, Hans Samuel; Siregar, Luthfi A. M. (Jurnal Online Pertanian Tropik, 2021)
The aim of the research was to determine the best paclobutrazol treatment to obtain superior quality seed potato cultivars. The research was conducted at the Tissue Culture Laboratory of Horticulture Technical Centre Service Unit, Gedung Johor, Medan, North Sumatra, Indonesia from January 2020 to March 2020. The complete randomized design with a single factor, 4 treatments, and 6 replications was used in this research. The results showed that the concentration of paclobutrazol affected the number of leaves, the shoots length, the number of shots, the number of nodes, the number of internodes, the stem diameter, and the percentage of roots formed but not significantly affected the number of roots. The M2 treatment, MS + 9 ppm paclobutrazol, showed the best treatment with an average plantlet performance value of 7.33 and the plantlets showed the compact morphology with larger stem diameter and smaller thick dark green leaves.